Understanding the Difference Between Chemical Changes and Physical Changes - Yoahana Elisabet; Catur Kurniawan (Indonesian Journal of Chemical Science and Technology (IJCST), 2022)
The purpose of this study is to distinguish physical changes and chemical changes. This study uses an experimental method, in which this experiment is carried out to prove data and hypotheses regarding changes in physics and chemical changes. The hypotheses and data that will be proven are the factors that influence physical changes and chemical changes, examples of physical changes and also chemical changes, as well as significant differences between physical and chemical changes. In this research, I used some tools and I need some materials. For the tools that used in this research were test tube holders, measuring pipettes, droppers, spirits lamp, clay triangle and gauze, beaker glass, test tubes and also the rack of test tubes, watch glass. While for the materials that needed are I2, CuSO4, Mg, HCl, CCl4, KI, wax, H2O.